"beside this corrupt and holy stream": Sacramental Water in Wendell Berry's Jayber Crow - Lambert, Christina J. (Christianity & literature, 2021)
This study of water in Jayber Crow helps illuminate the eschatological vision of Wendell Berry and shows how love for the earth can also manifest itself in a love for heaven, not by disdaining the earth but by embracing its sacramentality. Jayber's life is shaped by the river that runs through his story and influences him physically and spiritually. It is the river that guides him home, moves him to the camp house, shows him the beauty of living alongside of nature, baptizes him, and teaches him how to articulate his hope. Seen in this light, Jayber Crow acts as a clarion call for preserving sacramental realities such as water. This reading dwells in the intersection of blue-ecocriticism, ecotheology, and sacramental theology, showing how Jayber's story weaves together the spiritual and physical significance of water and teaches us that in order to heal our ecological relationships, we must heal our sacramental imaginations.